위법수집증거배제법칙의 실천적 과제 - 천진호(Chun Jin-Ho) (Tonga pŏphak, 2009)
The 17th Criminal Procedure Code of Presidential Committee on Judicial Reform led and established an the exclusionary Rule of illegally obtained Evidence provision. But until which degree scope of non-statement evidence applying the exclusionary Rule of illegally obtained Evidence about there is a various opinion. Specially after being supreme court decision(2007), the discussion sharply about this part, is advanced. The starting point of this dissertation the statement evidence when exception applies the exclusionary Rule of illegally obtained Evidence without, non-statement evidence, the exclusionary Rule of illegally obtained Evidence strictly, was not applied is. Relates with the application of the exclusionary Rule of illegally obtained Evidence of non-statement evidence and the contents which the theory and judicial precedent are presenting is the fiction could not be materialized from fact. But the theory and judicial precedent faithfully in principle of the lawful process which is provided in constitution, must interpret the exclusionary Rule of illegally obtained Evidence is a thing. Under evidence collecting from process the process is violated conclusively in constitution and infringes the right of the defendant and to the case which influences to entity judgment of event is a statement evidence, or, is, exception without applies an illegal collection evidence exclusion law a non-statement evidence, or must do. And like this interpretation the fact that is faithful to the lawsuit ideology which is a guarantee of rights of lawful process principle and the defendant of constitution as a matter of means that will do. KCI Citation Count: 8